2017
DOI: 10.1021/acs.analchem.7b03762
|View full text |Cite
|
Sign up to set email alerts
|

Background-Free Imaging of a Viral Capsid Proteins Coated Anisotropic Nanoparticle on a Living Cell Membrane with Dark-Field Optical Microscopy

Abstract: Exploring the diffusion dynamics of a viral capsid proteins (VCP)-functionalized nanocarrier on a living cell membrane could provide much kinetic information for the better understanding of their biological functionality. Gold nanoparticles are an excellent core material of nanocarriers because of the good biocompatibility as well as versatile surface chemistry. However, due to the strong scattering background from subcellular organelles, it is a grand challenge to selectively image an individual nanocarrier o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…[ 226,227 ] Ye and coworkers addressed this limitation using a polarization‐resolved dual channel imaging module. [ 228 ] The scattered signals of the interfering background from polarization‐resolved dual channels had negligible fluctuations while those of AuNRs had noticeable intensity differences, offering the opportunity to screen the interfering scattering background inside the cell by subtracting sequential images from a polarization‐resolved dual channel detector. With this strategy, the authors tracked the diffusion dynamics of viral capsid proteins (VCPs)‐coated AuNRs on living cell membrane and found that the particles displayed anomalous confined diffusion with randomly distributed large walking steps.…”
Section: Single Plasmonic Nanoprobes In Tracking the Motion Of Biomolmentioning
confidence: 99%
“…[ 226,227 ] Ye and coworkers addressed this limitation using a polarization‐resolved dual channel imaging module. [ 228 ] The scattered signals of the interfering background from polarization‐resolved dual channels had negligible fluctuations while those of AuNRs had noticeable intensity differences, offering the opportunity to screen the interfering scattering background inside the cell by subtracting sequential images from a polarization‐resolved dual channel detector. With this strategy, the authors tracked the diffusion dynamics of viral capsid proteins (VCPs)‐coated AuNRs on living cell membrane and found that the particles displayed anomalous confined diffusion with randomly distributed large walking steps.…”
Section: Single Plasmonic Nanoprobes In Tracking the Motion Of Biomolmentioning
confidence: 99%
“…Even some background scavenging reagents, background smoothing algorithms, etc., have been tried to reduce the intracellular scattering background, however, such problem has not been fully solved. [25][26][27][28] To detect small plasmonic nanoparticles, several types of photothermal imaging methods were developed based on plasmonic resonance absorption instead of scattering, since the absorption cross section of nanoparticles scales down with three power of particle size (slower than scattering). Laser scanning photothermal imaging is able to detect nanoparticles down to a few nanometers, and enable high resolution imaging of cellular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, for rod-like particles, comprehensive theoretical calculations illustrate that the diffusivity is much higher than that of their spherical counterparts in biological matrices 1618. Transient adhesive interactions with the host matrix play key roles in such anomalous diffusion 1921. Recent explorations also found that elongated rod-shaped inorganic particles exhibit a noticeable cellular translocation efficiency with size dimensions comparable to those of bacteria through carefully manipulating the surface chemistry 3.…”
Section: Introductionmentioning
confidence: 99%